The fuel of unparalleled recovery: Monetary policy in South Africa between 1925 and 1936 - Christie Swanepoel; Philip Fliers (Queen's University Centre for Economic History (QUCEH), 2021)
The newly established South African Reserve Bank (SARB) was tasked to protect the currency by navigating the interwar gold standard, and, from March 1933, maintaining parity with the Pound Sterling. We find that South Africa's exit from gold secured an unparalleled and rapid recovery from the Great Depression. South Africa's exit was accompanied by an inextricable link of the SARB's policy rate to the interest rate set by the Bank of England (BoE). This sacrifice of independent monetary policy allowed the SARB to fix the country's exchange rate without impeding the flow of gold to London. The SARB fuelled the economy by reducing its policy rates and accumulating gold. Had South Africa not devalued, the country would have suffered a severe depression and persistent deflation. An alternative to the devaluation, was for the SARB to pursue a cheap money strategy. By setting interest rates historically low, we find that South Africa could have achieved higher levels of economic growth, at the cost of higher inflation. Ultimately, South Africa's unparalleled recovery can be ascribed to the devaluation, however the change in the SARB monetary policy and the bank's control over the gold markets were of paramount importance.
Keywords: N14; N20; E42; E52; E58; F33; 330; monetary policy management; interwar gold standard; South Africa